Decrease in quality and quantity of clean water due to climate change - Wardiningsih, Jasmine Ayu; Masjud, Yunita Ismail (Journal of Earth Kingdom, 2024)
Climate change is a world phenomenon that is often discussed recently and has an impact, one of which is an increase in temperature. In addition, previous research says that climate change affects water resources found all over the world, where this temperature change is also enjoyed by the residents. The purpose of this research which means to know the impact of climate change (climate change) on the quantity and quality of hygienic water. Water is one of the natural resources that is needed all the time so that it is a very crucial human need. The method that will be carried out in this research is the mix method, namely the Library Study method and the qualitative method using descriptive lighting. with the impact of climate change which causes an increase in air temperature, causing faster evaporation of water, resulting in rapid reduction of groundwater. Conclusion : This reduced groundwater will affect the quantity and quality of hygienic water on earth. The results of this study are expected to be useful for the government and agencies related to the provision of hygienic water. Besides that, other people can learn to understand why there can be a decrease in the quality and quantity of hygienic water.